Current Concepts on Tissue Adhesive Use for Meniscal Repair—We Are Not There Yet: A Systematic Review of the Literature. Issue 5 (April 2022) - Marom, Niv; Ode, Gabriella; Coxe, Francesca; Jivanelli, Bridget; Rodeo, Scott A.
Background: Tissue adhesives (TAs) represent a promising alternative or augmentation method to conventional tissue repair techniques. In sports medicine, TA use has been suggested and implemented in the treatment of meniscal tears. The aim of this review was to present and discuss the current evidence and base of knowledge regarding the clinical usage of TAs for meniscal repair. Study Design: Systematic review; Level of evidence, 4. Methods: A systematic literature search was performed using the PubMed, Embase, and Cochrane Library databases for studies reporting on clinical outcomes of TA usage for meniscal repair in humans in the English language published before January 2020. Results: Ten studies were eligible for review and included 352 meniscal repairs: 94 (27%) were TA-based repairs and 258 (73%) were combined suture and TA repairs. Concomitant anterior cruciate ligament reconstruction was performed in 224 repairs (64%). All included studies utilized fibrin-based TA. Of the 10 studies, 9 were evidence level 4 (case series), and 8 reported on a cohort of ≤40 meniscal repairs. Rates of meniscal healing were evaluated in 9 of 10 studies, with repair failure seen in 39 repairs (11%). Conclusion: The use of TAs, specifically fibrin-based TAs, for meniscal repair shows good results as either an augmentation or primary repair of various configurations of meniscal tears. However, this review reveals an absence of comparative high-quality evidence supporting the routine use of TAs for meniscal repair and emphasizes the lack of an ideal TA designed for that purpose. Further high-quality research, basic science and clinical, will facilitate the development of new materials and enable testing their suitability for use in meniscal repair.